Aerobic exercise for vasomotor menopausal symptoms: A cost-utility analysis based on the Active Women trial - Goranitis, I; Bellanca, L; Daley, A; Thomas, A; Stokes-Lampard, H; Roalfe, A; Jowett, S (Public Library of Science, 2017)
Objective To compare the cost-utility of two exercise interventions relative to a control group for vasomotor menopausal symptoms. Design Economic evaluation taking a UK National Health Service and Personal Social Services perspective and a societal perspective. Setting Primary care. Population Peri- and postmenopausal women who have not used hormone therapy in the past 3 months and experience ≥ 5 episodes of vasomotor symptoms daily. Methods An individual and a social support-based exercise intervention were evaluated. The former (Exercise-DVD), aimed to prompt exercise with purpose-designed DVD and written materials, whereas the latter (Exercise-Social support) with community exercise social support groups. Costs and outcomes associated with these interventions were compared to those of a control group, who could only have an exercise consultation. An incremental cost-utility analysis was undertaken using bootstrapping to account for the uncertainty around cost-effectiveness point-estimates. Main outcome measure Cost per quality-adjusted life-year (QALY). Results Data for 261 women were available for analysis. Exercise-DVD was the most expensive and least effective intervention. Exercise-Social support was £52 (CIs: £18 to £86) and £18 (CIs: -£68 to £105) more expensive per woman than the control group at 6 and 12 months post-randomisation and led to 0.006 (CIs: -0.002 to 0.014) and 0.013 (CIs: -0.01 to 0.036) more QALYs, resulting in an incremental cost-effectiveness ratio of £8,940 and £1,413 per QALY gained respectively. Exercise-Social support had 80%-90% probability of being cost-effective in the UK context. A societal perspective of analysis and a complete-case analysis led to similar findings. Conclusions Exercise-Social support resulted in a small gain in health-related quality of life at a marginal additional cost in a context where broader wellbeing and long-term gains associated with exercise and social participation were not captured. Community exercise social support groups are very likely to be cost-effective in the management of vasomotor menopausal symptoms.